Analyzing BPJS Patient Satisfaction at Sumberjambe Public Health Center: A SERVQUAL Dimension Approach - Kusni; Amin Silalahi; Hanif Hadinata Utama (International Journal of Science and Environment (IJSE), 2026)
In primary healthcare ecosystems, maintaining optimal service quality is fundamental to achieving high patient satisfaction and sustaining public trust in universal health coverage programs. However, public health centers frequently face operational challenges in balancing high patient volumes with individual care expectations under the BPJS system. This research evaluates how healthcare service quality determines BPJS patient satisfaction at Sumberjambe Community Health Center, Jember Regency, employing the SERVQUAL framework. Applying a quantitative approach, 100 BPJS beneficiaries were recruited through accidental sampling to complete structured questionnaires. The dataset underwent multiple linear regression analysis via SPSS after meeting all prerequisites for validity, reliability, normality, homoscedasticity, and the absence of multicollinearity. Empirical results demonstrate that service quality substantially drives patient satisfaction (F = 18.450, p < 0.001), accounting for 49.5% of the variance (R2 = 0.495). While all individual SERVQUAL dimensions yielded statistically significant positive effects, Empathy surfaced as the strongest predictor β = 0.410). These insights underscore that optimizing interpersonal care, staff attentiveness, and communication channels is critical to elevating patient experience. Ultimately, this work validates the utility of SERVQUAL in primary healthcare settings and offers practical direction for institutional service refinement. Keywords: Service Quality, SERVQUAL, BPJS Patient Satisfaction, Public Health Center